Kreativitas Guru Pendidikan Agama Islam dalam Penguatan Karakter Spiritual Siswa di SMPN 12 Kota Bengkulu - Fanji Ramadhan; Zurifah Nurdin; Mindani Mindani (UIN Fatmawati Sukarno Bengkulu, 2022)
Religious education is education that provides knowledge and forms attitudes, personalities, and skills of students in practicing their religious teachings, which are carried out at least through subjects/lectures on all paths, levels, and types of education, teachers are professional educators with the main task of educating, teaching, guiding, directing, training, assessing and evaluating students, teachers as substitutes for parents at school have a very important and strategic role in efforts to foster religious behavior of students, teachers are central figures in organizing education, because teachers are figures needed to spur the success of their students according to initial observations, which were found to indeed require learning that connects to digital, because this supports teaching and learning activities and by using digital-based learning media that are easily captured by the students themselves, and in addition to learning and teaching activities at SMPN 12, there is also a tahfiz extracurricular that supports students to develop spiritual character with the learning in it, therefore each class has a different way of teaching, the qualitative research method is a research method based on the philosophy of post-positivism, used to research the conditions of objects that natural, (as opposed to experimental) where the researcher is the key instrument, data collection techniques are carried out by triangulation (combination), data analysis is inductive/qualitative, and qualitative research results emphasize meaning rather than generalization. Keywords: Creativity, Religious Education, Spiritual Character, students.